PRISONS AND PANDEMICS: SPECIAL REFERENCE TO PRISON SYSTEM REFORMS IN COVID-19 - Rakesh Kumar Handa; Vani Prakesh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Governance and the supervision of jails are exclusively following the State-run administrations. Prisons Act, 1894 governs the same and in accordance with the corresponding state administration instructions hand book. The jail inhabitants which has been in a constant increase during the past period. A majority of the penitentiary, almost nearly 96% populace, are gents, and roughly more than half are undertrials. The current article provides a general overview of the transnational commitments and recommendations one of such United Nations Standard Minimum Rules for the Treatment of Prisoners, 1955, which is with respect to nondiscrimination on various bases. It also addresses the wide spread difficulties of our country's prisons. The care of prisoners and summarize the different steps taken in the direction of custody restructuring in our nation.